Pengaruh tingkat suku bunga bi, inflasi, dan kurs terhadap non performing loan (studi empiris pada perusahaan sektor perbankan yang terdaftar di bursa efek indonesia (bei) periode tahun 2011-2013) - Rosita, Melinda; Taufik, Taufeni; Sofyan, Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of central bank interest rate Inflation and exchange rate against non-performing loans in the banking sector companies listed on the Stock Exchange for the 2011-2013.The method used in this research is to use multiple linear regression to determine the effect of central bank interest rate, Inflation and exchange rate as an independent variable against non-performing loans as a dependent variable against.The results of the hypothesis testing shows that the BI variable interest rates ,inflation and exchange rate effect on Non-Performing Loans. This is demonstrated by t-hitung for testing the value of the variable X1 (4,237), X2 (5,256) dan X3 (2,820) greater than t-table value ( 1.9869 ) and significant value of less than 0.05 .The resulting determinant coefficient is quite high. R values are obtained to demonstrate the correlation / relationship between variable interest rate of BI, inflation and the exchange rate against non- performing loans amounted to 0,541 , or 54.1 % .As for the value of R square is 0.292 which indicates that the ability of the independent variable is the variable interest rates of BI, inflation and exchange rate in explaining the variation of the dependent variable non-performing loans amounted to 29.2 % and the rest is explained by the other independent variables.Keywords: Non Performing Loan , interest rate BI , Inflation , Exchange